Sources and interpretation in ancient Judaism : studies for Tal Ilan at sixty - Piotrkowski, Meron M.; Dönitz, Saskia, 1973-; Herman, Geoffrey.; Ilan, Ṭal. (Ancient Judaism and Early Christianity, 2018)
Sources and Interpretation in Ancient Judaism: Studies for Tal Ilan at Sixty , a collection of studies by 14 scholars, is designed to honor an outstanding scholar in the field of Ancient Judaism, Tal Ilan. These studies reflect realms within the broad field of Ancient Judaism that are central to Ilan's scholarship: Second Temple literary sources and history, Gender, Jewish papyrology and rabbinic literature. The studies within this volume are of an interdisciplinary nature, offering new readings and interpretations of known sources such as Josephus and rabbinic texts, but also introducing the reader to an entirely new body of sources, namely Jewish papyri. The volume therefore aims to introduce specialists and non-specialists to new fields of research